Pengaruh sanitasi lingkungan terhadap kejadian penyakit kulit pada Santriwati di Pondok Pesantren Anshor Al-Sunah Kabupaten Kampar - Ramayanda Gusni; Ridwan Manda Putra; Bayhakki Bayhakki (SEHATI: Jurnal Kesehatan, 2021)
Skin disease can also be caused by poor personal hygiene behavior factors. The Anshor Al-Sunah Islamic boarding school in Kampar Regency is one of the Islamic boarding schools in Kampar Regency, and skin disease is a common health problem and is a major problem in the Anshor Al-Sunah Islamic boarding school in Kampar Regency. The incidence of skin disease in students in 2017 was recorded at 67 cases recorded at the UKS boarding school Anshor Al-Sunah, Kampar Regency, while in 2018 it increased to 86 cases. The research objective was to determine the effect of environmental sanitation on the incidence of skin disease among female students at the Anshor Al-Sunah Islamic Boarding School, Kampar Regency. This type of observational analytic quantitative research using a survey analysis research design approach. Survey analysis. The research was conducted at the Anshor Al-Sunah Islamic boarding school, Kampar Regency, Riau Province and from March to June 2020. Data collection tools used questionnaire sheets and observation sheets. The population was all students in the Anshor Al-Sunah Islamic boarding school, with a sample of 64 people, using proportional random sampling technique. Univariate, bivariate and multivariate analysis. The results of this study were ecological factors, personal hygiene factors that influenced the incidence of skin disease among students. It is hoped that pesantren managers will improve facilities and infrastructure in accordance with health standards to prevent skin disease transmission.